Zły i dobry nacjonalizm w interpretacji foucaultowskiej - Góra, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Contemporary discourse on controversial political phenomena and processes such as nationalism is often marked by assessments and valuations that change along with the needs of political centers of power. The same phenomenon can be subject to variable assessments depending on the current political regime. This is particularly evident in those areas of Europe that have repeatedly changed their state subordination over the last century. The author proposes a method of analyzing phenomena such as nationalism, inspired by the thought of French philosopher Michel Foucault. Using this method helps to neutralize the interpretative elements, which in the case of substantive analyses makes it easier to get to the heart of the matter, and in the case of emotive analyses reveal their lack of substance.Contemporary discourse on controversial political phenomena and processes such as nationalism is often marked by assessments and valuations that change along with the needs of political centers of power. The same phenomenon can be subject to variable assessments depending on the current political regime. This is particularly evident in those areas of Europe that have repeatedly changed their state subordination over the last century. The author proposes a method of analyzing phenomena such as nationalism, inspired by the thought of French philosopher Michel Foucault. Using this method helps to neutralize the interpretative elements, which in the case of substantive analyses makes it easier to get to the heart of the matter, and in the case of emotive analyses reveal their lack of substance.
Keywords: ﬁltr kognitywny; ideologia; autorytaryzm; interpretacja; uprzedmiotowienie; władza polityczna